Comprehensive chiroptical spectroscopy. Volume 2, - Berova, Nina; Polavarapu, Prasad L.; Nakanishi, Koji; Woody, Robert W. (Wiley, 2012)
"This book provides an introduction to the important methods of chiroptical spectroscopy in general, and circular dichroism (CD) in particular, which are increasingly important in all areas of chemistry, biochemistry, and structural biology. The book can be used as a text for undergraduate and graduate students and as a reference for researchers in academia and industry, with or without the companion volume in this set."--Resumé vydavatele